(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
Educational reforms are sustained on promises of innovation and improvement in learning. In many countries, the history curriculum swings between the continuity of the disciplinary code and the pretensions of change, a dispute which is generally biased in favor of the tradition. In Mexico, the curricular renewal takes place without having a diagnosis as a reference going through seven years with the 2011 curriculum. Instead of investigating the purposes, its correspondence with the rest of curricular dimensions or the formative conditions that are required to modify the practice, in this article the strategies, activities and the function of the students that are suggested in the history program are subjected to analysis. The text demonstrates that the didactic proposal and the conception of learning are homogeneous, canonical, contradictory, naive and theoretical.